The Effectiveness of Think Pair Share Cooperative Learning with the Assistance of Audiovisual Media for Chairil Anwar's Poem “Ibu” Listening to Poetry in Grade VIII at SMP Negeri 2 Sawangan - Safrina Ilmi Nur Azzah; Esti Swatika Sari; Berliana Wahyu Ningtyas (Cita konsultindo, 2025)
This research is a quantitative experimental study with the research topic on Indonesian language at SMP Negeri 2 Sawangan, namely poetry texts. This literary material is quite important for students to master because it is basic material in literature. The research design is a pretest-posttest group design in accordance with the objectives to be achieved. In this design, there are two classes, namely the experimental class and the control class. The objectives of this study are (1) to show that students taught using the think pair share (TPS) cooperative learning model assisted by audiovisual media and students taught using the conventional model have different learning outcomes in listening to poetry texts and (2) to show that eighth-grade students at SMP Negeri 2 Sawangan are more effective at learning poetry texts in the listening element with the think-pair-share (TPS) cooperative learning model assisted by audiovisual media. The results of the study indicate that applying the think-pair-share (TPS) cooperative learning model assisted by audiovisual media for Chairil Anwar's poem “Ibu” is more effective in improving the learning outcomes of eighth-grade students at SMP Negeri 2 Sawangan than applying conventional learning.